A template for building global partnerships: The Joining Forces conference goes across the Atlantic from the US to the UK. (December 2016) - Visovsky, Constance; Beedy, Dianne Morrison-
Abstract: Joining Forces is a comprehensive national initiative within the United States to mobilize all sectors of society to give service members and their families the opportunities and support they have earned. This national initiative begun in April 2012 was led by First Lady Michelle Obama and Dr. Jill Biden. The Joining Forces initiative is charged with enhancing the well-being and psychological health of the military family by providing mental health care services, integrating community-based services to reduce homelessness, substance abuse for veterans and military families. This manuscript addresses how one university with its global partners joined together to host an innovative conference addressing the research, education, and practice needs of healthcare professionals caring for military, veterans, and their families. Highlights: Recent wars and conflicts have led to physical and psychological heath issues in the military. The Joining Forces initiative has been adopted by many universities in the U.S. The JFRL conference has brought global partners together to address these issues.